Estimation of coupling factor in IPT systems using transmitter and receiver dimensional relationships - Narváez Acaro, Alexis Adrián; Carretero Chamarro, Claudio; Acero Acero, Jesús (Jornada de Jóvenes Investigadores del I3A, 2023)
In relation to the increasing implementation of inductive wireless power transfer systems in premium devices, this work presents an analysis using finite element models to establish a relationship between the coupling coefficient, the geometry of the windings, and the distance set between them. Also, simulation results have been validated with experimental measurements of two small coils facing each other at various distances.